2011
DOI: 10.4101/jvwr.v4i3.6129
|View full text |Cite
|
Sign up to set email alerts
|

Standards in Virtual Worlds Virtual Travel Use Case Metaverse1 Project

Abstract: Nowadays, tourism has become a very important industry in the international economy. Information and communication technologies are in constant development; they progress worldwide and across sectors. Their applications in tourism and tourist resources is rapidly increasing, reaching new, innovative and sometimes amazing results in terms of effectiveness, productivity, quality, and customer satisfaction. Exploring the interaction between technologies and tourism is difficult and challenging. Specifically, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For example, Wei et al's [21] research investigating the role of VR in enhancing the experience and behaviors of theme park visitors has shown that visiting theme park visitors or a destination through VR technology results in a strong intention to visit the destination or theme park. Similarly, for the museum experience, the VR tour generates a high intention to visit the museum [20][21][22][23][24][25][26][27][28][29][30]. By inference, VR technological tools [45] and rich content [38] make it possible to increase individuals' visit or travel intention because certain components of the VR visit experience, including telepresence, lead to a visit intention [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wei et al's [21] research investigating the role of VR in enhancing the experience and behaviors of theme park visitors has shown that visiting theme park visitors or a destination through VR technology results in a strong intention to visit the destination or theme park. Similarly, for the museum experience, the VR tour generates a high intention to visit the museum [20][21][22][23][24][25][26][27][28][29][30]. By inference, VR technological tools [45] and rich content [38] make it possible to increase individuals' visit or travel intention because certain components of the VR visit experience, including telepresence, lead to a visit intention [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, little research has paid attention to the phenomenon of VR in the tourist context [23,24]. Past research has investigated the role and effect of mental imagery in the context of a 2D website on the behavioral, emotional, and attitudinal responses of consumers [13][14][15][16][17][18][19][20][21][22][23][24][25]. Yet, to our knowledge, very little research has addressed mental imagery and VR, especially in the context of domestic tourism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation